Ethnobotany of local banana (Musa spp.) variety Loka Pere in West Sulawesi, Indonesia - JACOB SCOTT FETTIG; CAHYO PRAYOGO; MARTHEN P. SIRAPPA; SUKIMAN SUKIMAN; BURHANUDDIN BURHANUDDIN; SULTAN SULTAN; SYAHRUL KURNIAWAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Fettig JS, Prayogo C, Sirappa MP, Sukiman, Burhanuddin, Sultan, Kurniawan S. 2023. Ethnobotany of the local banana (Musa spp.) variety Loka Pere in West Sulawesi, Indonesia. Biodiversitas 24: 6472-6483. Compared to modern crop varieties, many farmers’ varieties are nutrient dense, stress tolerant, disease resistant and suited to local conditions. It is thought that increased utilization of farmers’ varieties in agrifood systems can improve rural livelihoods. One underutilized farmers’ variety is Loka Pere, a local banana (Musa spp.) in Majene District, West Sulawesi. The purpose of this research was to study ethnobotany of Loka Pere to develop its knowledge base regarding cultural importance, management and local perception of its potential, spatial dynamics and production constraints. Ethnobotany data was collected in the villages Adolang, Adolang Dhua, and Betteng through participatory observation, open-ended conversations, semi-structured interviews, and surveys. Descriptive, qualitative data was recorded alongside total use value and relative frequency of citation for its characteristic traits, ideal growth conditions, and limitations to production. Surveys included ranking and scaled perception questions. Loka Pere is an endemic farmers’ variety originating from the study area and may be locally adapted. It has a strong link to the local community’s identity - often called Manurung Adolang, or the “icon of Adolang” - and is the preferred banana of locals. It has unique phenotypic characteristics and uses, including use as a traditional fertility medicine. After approaching disappearance, local conservation projects and growing desire to utilize the resource led to its reintroduction to production systems. Respondents agreed they would benefit from its increased utilization, including development of processed products. Farmers described ideal conditions and processes for Loka Pere cultivation. It is often grown intercropped or in agroforestry systems. Limitations to production include wild boar, climate, and value chain. Loka Pere appears to be a farmers’ variety with high potential for regional development. Strengthening traditional knowledge related to its cultivation and use can aid in its reintegration into agrifood systems.